Decomposition of grasses in a South African savanna - Masubelele, Mmoto Leonard (Department of Biological Sciences, 2024)
Tropical and subtropical grasslands ecologists have ignored decomposition, because of the important role it plays in nutrient cycling, in terms of understanding how grass litter gets to the soil during the dry season. The major flaw is in the method~ employed to l investigate decomposition. In the prairies and steppes, litterbag methods employed investigate decomposition when litter is on the soil, even though the importance of carryover from standing litter is recognized. Standing litter results in high carryover which slows down decomposition thereby hindering productivity in the next growing season. I therefore decided to investigate the processes of photodegradation and microbial decomposition, as well as carryover and also how these processes differ between mesic and semi-arid grasslands. Since previous studies suggest that tallgrass prairies experience more carryover and slower decomposition than shortgrass prairies, I therefore hypothesized in this thesis that mesic grasslands will experience more carryover and slower decomposition than semi-arid grasslands. Results from this thesis showed that standing litter decomposition was slower than surface soil decomposition; hence photodegradation was slower than microbial decomposition. Photodegradation was important in controlling the rate of decomposition among the different grass species standing litter. Different grass species decomposed at different rates. Different plant traits were responsible for decomposition rates of standing litter and surface soil litter. Tensile strength and polyphenolic content were important during initial and final decomposition of standing litter whereas for the surface soil litter the same factors together with CIN ratio and lignin were important. Carryover existed in mesic grasslands but not so much in semi-arid grasslands. This implies that mesic grasslands are phylogenetically designed to bum while semi-arid grasslands are controlled by herbivory.